Simulation Analysis of Salt Diffusion at Wanquan River Estuary under Changing Environment - HAILAI Yibo; SHI Haoran; LIU Xiaoqing; LIU Jiao; FANG Mingyi; ZHANG Lanyue (Renmin Zhujiang)
The diffusion of offshore salt in inland rivers along with tidal waves has an important effect on the aquatic ecological environment of the estuary area.This paper,taking the Wanquan River Estuary as an example,used the Mike21 model to simulate the salinity distribution along the channel under different runoff and tidal levels and analyzed the change rules and leading factors.The results show that the river system and riverbed topography at the Wanquan River Estuary reduce the upward diffusion of salt propelled by the tide and that the salt is mainly distributed in the waters near the estuary.The salinity distribution along the upper reaches of the river decreases rapidly,and it basically remains unchanged when the tidal level increases by 0.1 m and 0.3 m,respectively.A sudden increase in salinity occurs where a curved or narrow channel changes the local water flow and salt accumulates.The upward diffusion range of salt is mainly affected by runoff. When the runoff reaches 106 m3/s and 148 m3/s,the tidal level needs to increase by 0.1 m and 0.3 m respectively before it has an impact.Different degrees of change in runoff and tidal level have different effects on salinity distribution at the estuary,and channel conditions play a key role.